The Spatial-Temporal Canvas That We Call the Stage: Text and Performance in Final Solutions - Ananya Ghoshal; Manivendra Kumar (Theatre Academy)
The article studies the significance and function of stage directions in Mahesh Dattani’s Final Solutions (1993). The stage directions propel the play-text to transcend into a performative script. Scholars Jisha Menon (2013) and Aparna Dharwadker (2005) commend Dattani’s ‘innovative’ dramaturgy for realistically representing the urban-middle-class home along with the complex social issues pervading this social milieu. This article argues for their assertion and extends their studies by examining the source of Dattani’s inventive stagecraft – his stage directions. It argues that Dattani challenges the label of dramatic text through his stage construction and stage directions. These directions add theatricality and render a visual appeal to the written text, which acts as a ‘drama’ for the students and critics of literature and a ‘fabel’ or a blueprint for other directors. The ostension of multiple levels of space-time in the text through stage directions reifies the mise-en-scene in the readers’ minds and also foregrounds Dattani’s reformist method of creating a conflict in his readers/audiences’ minds. Using a comparative analysis of the stage directions in the play-text by Dattani and a stage production by the Delhi-based Asmita Theatre under the direction of Arvind Gaur, it foregrounds Dattani’s extravagant and complex construction of the stage. It studies his distinct usage of the stage as a ‘spatial-temporal’ entity and establishes that Dattani’s stage directions are quintessential to his reformist agendas.